Smart structure integrity monitoring using transient response. - Iong, Kuoc-Vai. (University of Ottawa (Canada), 1997)
Applications of smart structures equipped with real time monitoring of structural integrity are expanding rapidly. In the present thesis, a non-destructive testing method was used to detect damage in a simple beam-like smart structure. In this study, two continuous beams perfectly connected, one of them equipped with a piezoceramic sensor and two piezoceramic actuators, were used to identify the changes in the boundary conditions. A non-destructive damage detection method for this simple smart structure was applied to two extreme cases. These cases were: two beams with a perfect connection and the original beams completely disconnected. Transient responses for the two cases were compared and the differences were analyzed for detecting the presence of damage. To illustrate the approach, the classic Euler-Bernoulli beam model for vibration analysis was used. Computer simulations based on the analytical modeling were performed. A quantitative measure of the safety of the beam and an index of safety were introduced. Experimental verification of the concept of the method was successfully carried out. The results confirm the feasibility of the proposed structural integrity monitoring method.
Keywords: Engineering, Mechanical.